Surface Wettability and Colour Change of Betung Bamboo Strands Treated with 1% NaOH under Various Immersing Times - Rio Ardiansyah Murda; Sena Maulana; Silvia Uthari Nuzaverra Mayang Mangurai; Fajar Aditya Julyatmojo; Astri Aulia Suwanda; Muhammad Saeful Fadlan (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM), Institut Teknologi Sumatera, Lampung Selatan, Lampung, Indonesia, 2022)
Bamboo was a material with enormous potential to be used as raw material for various purposes. This material has good properties for structural purposes such as buildings and furniture or converted to a composite product such as bamboo oriented strand board (BOSB). This study was aimed to determine the wettability properties and the colour change of Dendrocalamus asper bamboo strands after alkali immersing treatment with 1% NaOH solution. The treatments were carried out for 1, 2, and 3 hours, respectively. The wettability of surfaces is quantified by computing the value of the K parameter or the contact angle change rate constant. Meanwhile, the colour change parameter of bamboo strands was quantified by portable colour difference meter CDX – 105 to determine the brightness intensity of a combination of red–green and blue-yellow. The results show that the wettability properties of bamboo strands were getting better after the treatments. On the other hand, the bamboo strands' colour was darker due to the alkali immersion treatment. The optimum duration of alkali immersing treatment with 1% NaOH was 2 hours.